Nutritive value of expeller/cold-pressed canola meal and pre-pressed solvent-extracted carinata meal for broiler chicken - Atta Kofi Agyekum (Elsevier, 2022)
ABSTRACT: A study was conducted to evaluate standardized ileal digestibility (SID) of amino acids (AA) and nitrogen-corrected apparent metabolizable energy (AMEn) values of pre-pressed solvent-extracted carinata meal (SE-carinata meal) and expeller/cold-pressed canola meal (ECP-canola meal) for broilers. Two hundred and forty broiler chicks were divided into 40 groups of 6 birds/group and fed 4 diets in a completely randomized design (10 groups/diet) from 14 to 21 d of age. The diets were cornstarch-based containing SE-carinata meal, ECP-canola meal, or pre-pressed solvent-extracted canola meal (SE-canola meal; reference feedstuff) as the sole protein source, and N-free diet. Digestibility of AA and N retention for feedstuffs was determined by the direct method, whereas energy retention of feedstuffs was determined by difference from the N-free diet. On DM basis, SE-canola meal, ECP-canola meal, and SE-carinata meal contained 43, 36, and 50% CP; 2.60, 2.21, and 1.82% Lys; 32, 29, and 27% neutral detergent fiber, and 1.1, 15.3, and 0.88% ether extract, respectively. On DM basis, the AMEn value was lowest (P < 0.05) for SE-carinata meal (1,295 kcal/kg), intermediate (P < 0.05) for SE-canola meal (1,608 kcal/kg), and greatest (P < 0.05) for ECP-canola meal (1,994 kcal/kg). The SID values of indispensable AA for ECP-canola meal were greater (P < 0.05) than those for SE-canola meal or SE-carinata meal. The SID values of all indispensable AA (except Gly, Lys, and Trp) for SE-carinata meal were greater (P < 0.05) than those for SE-canola meal. The SE-canola meal and SE-carinata meal did not differ in SID of Gly and Trp; however, SE-carinata meal had lower (P < 0.05) SID of Lys than SE-canola meal. The results indicate that ECP-canola meal fed in this study could be a good source of AA and energy for broilers. Results also indicate that SE-carinata meal fed in this study could be an attractive AA source for broiler diet, but could benefit from Lys fortification due it its low SID Lys value.